ACCOUNTING OF FIXED ASSETS AND INTANGIBLE ASSETS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Fixed assets and intangible assets represent significant components of an organization's resources and play a crucial role in business operations and financial reporting. Proper accounting of these assets ensures the accuracy of financial statements, supports effective management decisions, and contributes to sustainable economic development. This article examines the concepts, classification, recognition, valuation, and accounting procedures related to fixed assets and intangible assets. Particular attention is given to depreciation, amortization, and the importance of accurate accounting practices in modern enterprises.
Keywords: accounting, fixed assets, intangible assets, depreciation, amortization, financial reporting, asset valuation, accounting standards.